Hypnotic Effect of A. absinthium Hydroalcoholic Extract in Pentobarbital-Treated Mice - Hassan Rakhshandeh; Amirhossein Heidari; Ali Mohammad Pourbagher-Shahri; Roghayeh Rashidi; Fatemeh Forouzanfar (Neurology Research International)
Background. Current drugs used in the management of insomnia are associated with side effects. The use of medicinal herbs for insomnia treatment has recently been suggested. Objective. The present study aimed to determine the hypnotic activity of the hydroalcoholic extract of Artemisia absinthium (A. absinthium) in mice. Method. The toxicity of A. absinthium extract is assessed by their lethal dose 50% (LD50), and cytotoxicity evaluation was also done with PC12 cell lines by MTT assay. A. absinthium extract (25, 50, 100, and 200 mg/kg) and 3 fractions (n-butanol fraction (NBF), ethyl acetate fraction (EAF), and aqueous fraction (AQF)) were administered intraperitoneally30 minutes before 30 mg/kg pentobarbital intraperitoneal injection; after that, the sleeping time and sleep latency were recorded. Results. The LD50 value was 2.4 g/kg. The extracts tested showed no negative effect on the proliferation of PC12 cells. A. absinthium extract increased the duration of pentobarbital-induced sleep at doses of 100 and 200 mg/kg (P<0.01-P<0.001). Similarly, AQF, EAF, and NBF at 200 mg/kg could increase sleep duration (P<0.05). The sleep latency was decreased by A. absinthium extract at doses of 100 and 200 mg/kg (P<0.05-P<0.01), AQF (P<0.05), and EAF (P < 0.05). Besides, flumazenil reversed the hypnotic effect of A. absinthium extract (P<0.05). Conclusion. A. absinthium extract probably demonstrated sleep-enhancing effects by regulating GABAergic system.